Impact of gamma irradiation on structural, thermal, and rheological properties of talipot palm (Corypha umbraculifera L.) starch: a stem starch. (November 2022) - Navaf, Muhammed; Sunooj, Kappat Valiyapeediyekkal; Aaliya, Basheer; Sudheesh, Cherakkathodi; Akhila, Plachikkattu Parambil; Sabu, Sarasan; Sasidharan, Abhilash; George, Johnsy
Abstract: Talipot palm ( Corypha umbraculifera L.) is a non-conventional source of stem starch. The starch obtained from the trunk of the talipot palm was subjected to various doses of irradiation (20 kGy, 50 kGy, 80 kGy, and 100 kGy). The effect of this high dose irradiation on functional, pasting, thermal and rheological properties was studied. The irradiation considerably decreased the amylose content, pH, swelling index, and relative crystallinity, and it increased the carboxyl content and solubility. The L* value, water absorption capacity, and oil absorption capacity were also increased by irradiation. The pasting parameters like pasting temperature, peak viscosity, and final viscosity were considerably decreased by irradiation. The paste clarity and light transmittance of irradiated starches were high at any point of storage. The gel hardness was decreased by γ-irradiation up to a radiation dose of 50 kGy. The FTIR analysis did not show any evidence for the formation of new functional groups. The gelatinization properties, storage modulus, and loss modulus were decreased by irradiation. The principal component analysis showed a good relationship among the different parameters studied. Highlights: Starch was subjected to gamma irradiation (20, 50, 80 and 100 kGy). Swelling capacity and pasting parameters decreased by irradiation. Gel hardness was considerably decreased by irradiation. Irradiated starch exhibited a high light transmittance and paste clarity. The enthalpy of gelatinization was greatly decreased by irradiation.